Teaching Mahārat al-Kitābah through Imlā’, Inshā’, and Problem-Based Learning: A Study at Madrasah Aliyah - Vanesya Vickri Syakara; Nur Fatmawati; Moh. Nurul Huda; Muasomah Muasomah (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
This study aims to comparatively analyze the Imla’, Insya’, and Problem Based Learning (PBL) methods in teaching mahārah kitābah at the Madrasah Aliyah level. Arabic writing skills remain one of the most challenging competencies for students due to linguistic complexity, limited instructional time, and the dominance of traditional teaching approaches. This research employed a qualitative library research design by examining books and recent scholarly journal articles relevant to Arabic writing pedagogy. Data were collected through documentation techniques and analyzed using thematic comparative analysis focusing on instructional characteristics, strengths, weaknesses, and contextual implementation of each method. The findings reveal that the Imla’ method is effective in improving orthographic accuracy and reducing writing errors, Insya’ particularly guided composition enhances students’ expressive ability and sentence structure, while PBL promotes critical thinking, collaboration, and contextual writing competence. However, each method also presents limitations when applied independently. Therefore, this study concludes that an integrative instructional approach combining Imla’, Insya’, and PBL is the most relevant strategy for improving Arabic writing skills in Madrasah Aliyah. The results contribute both theoretically to Arabic language teaching methodology and practically for teachers in designing adaptive and effective writing instruction.Key words: Arabic writing skills; Imla’; Insya’; Problem Based LearningPenelitian ini bertujuan untuk menganalisis secara komparatif metode Imla’, Insya’, dan Problem Based Learning (PBL) dalam pembelajaran mahārah kitābah di Madrasah Aliyah. Keterampilan menulis bahasa Arab masih menjadi kompetensi yang sulit dikuasai siswa karena kompleksitas linguistik, keterbatasan waktu pembelajaran, serta dominasi metode tradisional. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi pustaka, melalui telaah terhadap buku dan artikel jurnal ilmiah terbaru yang relevan dengan pembelajaran kitābah. Teknik pengumpulan data dilakukan melalui dokumentasi, sedangkan analisis data menggunakan analisis tematik komparatif berdasarkan karakteristik, kelebihan, kelemahan, dan konteks penerapan masing-masing metode. Hasil penelitian menunjukkan bahwa metode Imla’ efektif dalam meningkatkan ketepatan ejaan dan meminimalkan kesalahan tulis, metode Insya’ khususnya Insya’ Muwajjah mampu mengembangkan ekspresi ide dan struktur kalimat, sementara PBL mendorong keterampilan berpikir kritis, kolaborasi, dan penulisan kontekstual. Namun, setiap metode memiliki keterbatasan jika diterapkan secara terpisah. Oleh karena itu, penelitian ini menyimpulkan bahwa integrasi ketiga metode tersebut merupakan strategi paling relevan untuk meningkatkan mahārah kitābah siswa Madrasah Aliyah.Kata kunci: mahārah kitābah; Imla’; Insya’; Problem Based Learning